Pediatric eye movement-based perimetry: progress, pitfalls, and prospects - Boethun, Anna; von Holstein, Sarah Linea; Mathiasen, René; Kolko, Miriam; Cornelissen, Frans W.; Goossens, Jeroen; Nordhjem, Barbara Johanne Thomas (Frontiers in Ophthalmology, 2025)
IntroductionEye movement-based perimetry (EMP) is a promising, non-invasive approach for visual field assessment, particularly in pediatric populations where standard automated perimetry often fails. However, completion rates in prior pediatric EMP studies have ranged from 41 to 81%, and reasons for unsuccessful testing are seldom reported.ObjectiveIn this perspective article, we aim to highlight practical barriers and design gaps in EMP systems for children, with a focus on clinical use.ObservationsFrom our clinical experience with testing two commercially available EMP systems in children (21 patients with brain tumors and 19 age-matched controls), we observed recurring challenges, including poor ergonomic fit, inadequate calibration of eye tracker, and insufficient attention management strategies. These issues frequently led to data loss and incomplete tests, underscoring the gap between current technology and pediatric clinical needs. We outline solutions informed by technological development, vision science and clinical ophthalmology.ConclusionPediatric testing experience must inform EMP design to ensure accessibility and reliability. Our observations highlight the need for clinician-engineer-scientist collaboration, with innovations likely to benefit not only children but also adults with similar testing challenges.